Adjusting to life in a residential aged care facility: Perspectives of people with dementia, family members and facility care staff. Issue 21 (21st July 2019) - Davison, Tanya E.; Camões-Costa, Vera; Clark, Anna
Abstract: Aims and objectives: To determine factors that facilitate or impede adjustment to residential aged care (RAC) from the perspectives of residents with dementia, families of residents with dementia and facility staff. Background: The transition to a RAC facility can be highly stressful for people with dementia and their families, but we lack an understanding of how people with dementia experience this transition. Knowledge on adjustment to the new environment is essential in order to develop procedures and interventions that better support residents. Design and methods: This study consisted of interviews with 12 residents with dementia who had resided at a RAC facility for six months or less; 14 family members of RAC residents with dementia; and 12 RAC facility staff members. Parallel interview schedules were constructed, with questions on the experience of relocating to RAC for a person with dementia and views on enablers and barriers to successful adjustment. Thematic analysis guided the analysis of data. The study adhered to the consolidated criteria for reporting qualitative research (COREQ) guidelines (see Supplementary File S1). Results: Adjustment to RAC appeared variable, with several residents reporting poor acceptance of their circumstances several months after the relocation. The three groups were largely congruent regarding the importance of support from families and staff, and the development of new relationships with other residents, but not all residents had succeeded in forming friendships. The provision of meaningful activities and opportunities to exert autonomy day‐to‐day were seen as critical, but staff experienced challenges in providing individualised care due to lack of dedicated time to engage with residents. Conclusion and relevance to clinical practice: There is a need for evaluated interventions to help people with dementia to successfully transition to RAC. Attention should be paid to the way in which care is coordinated within the RAC sector, to enable staff to provide individualised approaches to facilitate adjustment.